Fundamental study and modification of Kenaf fiber reinforced polylactic acid bio-composite for 3D printing filaments - Alaa, Moustafa; Abdan, Khalina; Ching Hao, Lee; Rafiqah, Ayu; Al-Talib, Ammar; Huzaifah, Muhammad; Mazlan, Norkhairunnisa (Elsevier BV, 2023)
Additive manufacturing (AM) of green bio-composites had been growing recently to valorize agricultural waste and attain green fillers capable of reducing bioplastic costs, without compromising the material processability and performance. Several problems such as poor surface adhesion and the hydrophilic nature were repeatedly reported to affect the properties of the extruded bio-composites and their lifetime. Green treatment methods such as Superheated steam (SHS) had been used to improve the natural fibers flaws without any environmental impact. 3D printing filaments were extruded by a single screw extrusion machine using Polylactic Acid (PLA) matrix reinforced at 10 wt% using both untreated and SHS-treated fibers at 230 °C which were used to print testing samples using Fused deposition modelling (FDM) 3D printer. From the tensile result, it was found that the untreated filament (PLA-KF10) had the highest ultimate strength with 27.27 MPa compared to 13.20 MPa for the treated fiber filament (PLA-SHSKF10). This behavior is supported by the Dynamic mechanical analysis (DMA) which had values of 1389 MPa compared to 1267 MPa respectively. DMA results showed a better of the PLA-SHSKF10 compared to the PLA-KF10 with values of 222.15 MPa compared to 215.84 MPa in the Loss modulus, and 1.46 and 1.04 for the Tan delta values. The use of treated fibers also reduced water absorption from 20.68% to 14.81%.